Characterization of a Hexavalent Chromium Reducing Bacterial strain isolated from Tannery Effluents of Kolkata - R R Ray, Dr (International Journal of Pharmaceutical & Biological Archive, 2013)
Characterization of a Hexavalent Chromium Reducing Bacterial strain isolated from Tannery Effluents of Kolkata